2021
DOI: 10.3390/foods10102436
|View full text |Cite
|
Sign up to set email alerts
|

Auricularia auricula Melanin Protects against Alcoholic Liver Injury and Modulates Intestinal Microbiota Composition in Mice Exposed to Alcohol Intake

Abstract: The potential effects of Auricularia auricula melanin (AAM) on the intestinal flora and liver metabolome in mice exposed to alcohol intake were investigated for the first time. The results showed that oral administration of AAM significantly reduced the abnormal elevation of serum total triglyceride (TG), cholesterol (TC), low density lipoprotein cholesterol (LDL-C), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), and significantly inhibited hepatic lipid accumulation and steatosis in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
(74 reference statements)
1
8
1
Order By: Relevance
“…ABC transporters have been considered important participants in the self-protection of zebrafish embryos against environmental pollutants such as BDE-47 and BDE-209. Specifically, this study found that DBDPE treatment led to a significant increase in metabolites such as betaine, melibiose, and maltotriose, which are involved in the pathway associated with ABC transporters in zebrafish larvae (Figure C). Betaine acts as the methyl donor and could regulate lipid metabolism, and maltotriose is the primary product from dietary starch and maltodextrin, which is ultimately digested to glucose. , Therefore, the potential effects on glucose and lipid metabolism were further validated in zebrafish larvae upon DBDPE exposure (Figure G). We found that the glucose levels were significantly increased, while the pyruvic acid contents were significantly decreased in zebrafish larvae exposed to 400 μg/L DBDPE ( P < 0.05; Figure G1,G2).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC transporters have been considered important participants in the self-protection of zebrafish embryos against environmental pollutants such as BDE-47 and BDE-209. Specifically, this study found that DBDPE treatment led to a significant increase in metabolites such as betaine, melibiose, and maltotriose, which are involved in the pathway associated with ABC transporters in zebrafish larvae (Figure C). Betaine acts as the methyl donor and could regulate lipid metabolism, and maltotriose is the primary product from dietary starch and maltodextrin, which is ultimately digested to glucose. , Therefore, the potential effects on glucose and lipid metabolism were further validated in zebrafish larvae upon DBDPE exposure (Figure G). We found that the glucose levels were significantly increased, while the pyruvic acid contents were significantly decreased in zebrafish larvae exposed to 400 μg/L DBDPE ( P < 0.05; Figure G1,G2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Betaine acts as the methyl donor and could regulate lipid metabolism, and maltotriose is the primary product from dietary starch and maltodextrin, which is ultimately digested to glucose. 47,48 Therefore, the potential effects on glucose and lipid metabolism were further validated in zebrafish larvae upon DBDPE exposure (Figure 2G). We found that the glucose levels were significantly increased, while the pyruvic acid contents were significantly decreased in zebrafish larvae exposed to 400 μg/L DBDPE (P < 0.05; Figure 2G1,G2).…”
Section: Dbdpe-induced Metabolomicmentioning
confidence: 99%
“…Many nutrients can promote the relative abundance of A. muciniphila in various models ( Table 1 ), [ 14,45–81 ] while others have been shown to decrease the relative abundance of A. muciniphila ( Table 2 ). [ 5,82–87 ] The presence of A. muciniphila has often been described as associated with good health, showing a correlation with α‐diversity of the gut microbiota, which represents the species richness or the number of species in the intestinal ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increases in MCP-1 secretion are strongly associated with IL-1β and can activate multiple inflammatory pathways leading to the secretion of IL-6, TNF-α, and G-CSF (Huang et al, 2022). IL-6 is a well-established inflammation-promoting cytokine secreted by a variety of cell types (Mauer et al, 2015;Lin et al, 2021). Abnormal levels of TNF-α disturb the immune system by activating TNF receptors and up-regulating the downstream pathways and regulatory molecules, including NF-κB, MAPKs, caspases, and ROS/RNS (Blaser et al, 2016).…”
Section: Discussionmentioning
confidence: 99%